2016
DOI: 10.1093/rheumatology/kev441
|View full text |Cite
|
Sign up to set email alerts
|

An EULAR study group pilot study on reliability of simple capillaroscopic definitions to describe capillary morphology in rheumatic diseases

Abstract: This multicentre, international study showed moderate reliability of simple capillaroscopic definitions for describing morphology of capillaries by rheumatologists with varying levels of expertise. Novices were capable of distinguishing normal from abnormal capillaries by means of a 1-h training session. In future studies, the class not evaluable may be obsolete.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
123
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 132 publications
(130 citation statements)
references
References 11 publications
3
123
0
4
Order By: Relevance
“…Various previous studies report reliability of high magnification nailfold capillaroscopy, highlighting the implied need for standardisation [12,13,[16][17][18][19][20][21][22][23][24]. Some included only two observers [12,16,17,20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various previous studies report reliability of high magnification nailfold capillaroscopy, highlighting the implied need for standardisation [12,13,[16][17][18][19][20][21][22][23][24]. Some included only two observers [12,16,17,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…A very recent study from Smith et al reported that when observers were asked to assess a single capillary ('normal', 'abnormal' or 'not evaluable') an unspecified proportion of the images were ranked 'not evaluable' [23]. This indicates the complexities of capillaroscopic analysis, and how challenging interpretation can be at the individual capillary level as well as at both the 'patient' level (averaging across fingers) [17,21] and image/'finger' level (as in the current study).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the dermatoscope with magnification of the order of x10 is a small, inexpensive and easily portable piece of equipment that has been suggested to be comparable to videocapillaroscopy in routine clinical practice. As the study of capillary morphology provides clinically relevant information in the management of patients with scleroderma-spectrum diseases, the development of specific software to standardize and automatize the analysis is ongoing [3][4].…”
Section: Francesca Ingegnoli Academic Rheumatology Unit Universita Dmentioning
confidence: 99%
“…In 2011, Mahbub and Harada23 reported that few capillaroscopic studies on VWF existed, and the ones that did commonly focused on capillary abnormalities on limb dropouts and/or morphology alterations. Smith et al 24 standardised the method of interpreting individual capillaries reliably and introduced a more practical way for novices to distinguish normal capillaries and abnormal capillaries individually after a quick training course.…”
Section: Introductionmentioning
confidence: 99%